Reproducing the Universe: a comparison between the EAGLE simulations and the nearby DustPedia galaxy sample. Issue 2 (4th April 2020) - Trčka, Ana; Baes, Maarten; Camps, Peter; Meidt, Sharon E; Trayford, James; Bianchi, Simone; Casasola, Viviana; Cassarà, Letizia P; De Looze, Ilse; De Vis, Pieter; Dobbels, Wouter; Fritz, Jacopo; et al.
ABSTRACT: We compare the spectral energy distributions (SEDs) and inferred physical properties for simulated and observed galaxies at low redshift. We exploit UV-submillimetre mock fluxes of ∼7000 z  = 0 galaxies from the EAGLE suite of cosmological simulations, derived using the radiative transfer code skirt . We compare these to ∼800 observed galaxies in the UV-submillimetre range, from the DustPedia sample of nearby galaxies. To derive global properties, we apply the SED fitting code cigale consistently to both data sets, using the same set of ∼80 million models. The results of this comparison reveal overall agreement between the simulations and observations, both in the SEDs and in the derived physical properties, with a number of discrepancies. The optical and far-infrared regimes, and the scaling relations based upon the global emission, diffuse dust, and stellar mass, show high levels of agreement. However, the mid-infrared fluxes of the EAGLE galaxies are overestimated while the far-UV domain is not attenuated enough, compared to the observations. We attribute these discrepancies to a combination of galaxy population differences between the samples and limitations in the subgrid treatment of star-forming regions in the EAGLE-skirt post-processing recipe. Our findings show the importance of detailed radiative transfer calculations and consistent comparison, and provide suggestions for improved numerical models.